2014
DOI: 10.1002/ar.22967
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VI Localization and Expression in Striated Muscle Pathology

Abstract: Myosin VI (MVI) is a unique unconventional myosin translocating, unlike other myosins, towards the minus end of actin filaments. It is involved in numerous cellular processes such as endocytosis, intracellular trafficking, cell migration, and transcription. In mammalian skeletal muscles it localizes mainly to sarcoplasmic reticulum and is also present within the muscle nuclei and at the neuromuscular junction (Karolczak et al. Histochem Cell Biol 2013; 23:219-228). We have also shown that in denervated rat hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Notably, its amount was significantly increased in atrophic fibers of muscle biopsies obtained from patients with several myopathies (Karolczak et al 2014). In humans, a point mutation (H246R) within the MVI gene was associated with cardiac hypertrophy, suggesting an important role of this molecular motor in striated muscles (Mohiddin et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, its amount was significantly increased in atrophic fibers of muscle biopsies obtained from patients with several myopathies (Karolczak et al 2014). In humans, a point mutation (H246R) within the MVI gene was associated with cardiac hypertrophy, suggesting an important role of this molecular motor in striated muscles (Mohiddin et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that MVI plays important roles both in skeletal and cardiac muscle [ 13 , 15 ] and in C2C12 myoblasts [ 14 ]. To further explore MVI function in myogenic cells, we performed a search for its binding partners by means of an affinity chromatography with the GST-tagged globular tail domain of MVI (GST-MVI-GT) used as a bait.…”
Section: Resultsmentioning
confidence: 99%
“…One of the mutations, a H246R mutation within the human MVI motor domain, was also found to be associated with hypertrophic cardiomyopathy [ 12 ] suggesting important role(s) of this motor in striated muscle. Indeed, our recent work has shown that in striated muscle as well as in myogenic cells MVI could be involved in the organization/maintenance of the sarcoplasmic reticulum, Golgi apparatus, adhesive structures (and intercalated discs in case of cardiac muscle), nuclei, and the neuromuscular junction [ 13 15 ]. We found that in skeletal muscles MVI might interact with TOM1 (target of myb1 homolog isoform 1, a protein involved in intracellular transport and autophagy), FMRP (fragile X mental retardation autosomal homolog 1, a protein involved in mRNA transport), and hnRNP proteins (involved in the RNA transport and maturation) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are about 20 classes of these molecules (Krendel and Mooseker, ; Hartman and Spudich, ). Redowicz and coworker (Karolczak et al, ) review the distribution and roles of one of these unconventional myosins, myosin VIA, in healthy and in diseased striated muscle cells.…”
Section: Contributions In This Issuementioning
confidence: 99%